The Practice of Networked Learning: Experiences of design and participation - McConnell, David; Noakes, Nick; Rowe, Patricia; Stewart, William (Proceedings of the International Conference on Networked Learning, 2000)
This paper considers a continuing professional development networked learning Masters course which is about learning and teaching via the Internet. In the paper, one tutor and three course participants describe their experiences of the course as a way of illuminating some issues around the design and participation of networked learning. We start with an over view of the course, which is followed by the personal perspectives. We finish with some general remarks about learning and teaching in networked learning environments.